SCIENTIFIC-THEORETICAL FOUNDATIONS OF TAXATION FOR THE USE OF NATURAL RESOURCES (Emergent: Journal of Educational Discoveries and Lifelong Learning (EJEDL), 2023)
This article provides general information about the scientific and theoretical basis of taxation for the use of natural resources. It explores the principles, concepts, and models that underpin taxation policies related to the extraction and use of natural resources. In the context of taxation, it is important to obtain sustainable income, protect the environment and make optimal use of natural resources. In addition, challenges and opportunities for designing effective tax systems that balance economic development and environmental protection are examined. It concludes with recommendations for developing a fair, transparent, and efficient tax system that helps tax authorities manage natural resources responsibly and supports long-term economic and environmental goals.